Basophil activation testing in occupational respiratory allergy to low molecular weight compounds. Issue 2 (April 2019) - Vera-Berrios, Rosialzira Natasha; Feary, Johanna; Cullinan, Paul
Abstract : Purpose of review: There is an unmet need for better immunological tests in cases of suspected occupational asthma to many workplace chemicals; here we consider the basophil activation test (BAT), a potential alternative to the detection of specific IgE antibodies. Recent findings: BAT is fairly widely used in general allergy services; and there is increasing experience of its use in the diagnosis of occupational allergy to low molecular weight agents and chemicals including wood dusts, persulphates, antibiotics and latex. Summary: There is potential for BAT to become a useful tool in the clinical consideration of occupational asthma and of its mechanisms, and even to take a place in a Bayesian-based diagnostic algorithm. Further development will only occur if specialist centres with appropriate facilities, and preferably in collaboration, contemplate its use.